STRATEGI KOMUNIKASI PERSUASIF DALAM MENANGANI KONFLIK BULLYING DI PESANTREN: SEBUAH KAJIAN LITERATUR - Ramadhani, Nia; Syarifah, Siti Fatimatus; Hanafiah, Gesha Ayu; Zahroh, Ulfa Malikatuz; Mu'alimin, Mu'alimin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Bullying is increasingly prevalent in educational environments, including in Islamic educational settings like pesantren. This research aims to examine conflict management strategies for bullying within these settings using persuasive communication methods. The study employs a qualitative methodology with a library research approach. Findings indicate that bullying in pesantren is generally triggered by internal factors, such as personality and family upbringing, as well as external factors, like strict pesantren culture, seniority, and limited parental supervision. Based on the research results, persuasive communication strategies have proven effective, as they not only reduce potential conflicts but also create a conducive environment for character development among students. Thus, persuasive communication can serve as an alternative method for addressing conflicts in pesantren.